2013
DOI: 10.1073/pnas.1308362110
|View full text |Cite|
|
Sign up to set email alerts
|

Dysregulation of PAD4-mediated citrullination of nuclear GSK3β activates TGF-β signaling and induces epithelial-to-mesenchymal transition in breast cancer cells

Abstract: Peptidylarginine deiminase 4 (PAD4) is a Ca 2+ -dependent enzyme that converts arginine and methylarginine residues to citrulline, with histone proteins being among its best-described substrates to date. However, the biological function of this posttranslational modification, either in histones or in nonhistone proteins, is poorly understood. Here, we show that PAD4 recognizes, binds, and citrullinates glycogen synthase kinase-3β (GSK3β), both in vitro and in vivo. Among other functions… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

4
97
1
2

Year Published

2014
2014
2023
2023

Publication Types

Select...
10

Relationship

2
8

Authors

Journals

citations
Cited by 117 publications
(104 citation statements)
references
References 39 publications
4
97
1
2
Order By: Relevance
“…Indeed, citrullination critically regulates embryogenesis (21,22), epithelial-to-mesenchymal transformation (23), and pluripotency of embryonic stem cells (24). In addition, PAD4-mediated citrullination of histones is essential for the formation of neutrophil extracellular traps (NETs) (25)(26)(27), which can induce the expression of inflammatory cytokines, such as IL-6 and IL-18, as well as CCL20 and ICAM-1 from fibroblast-like synoviocytes (28).…”
Section: It Was Recently Demonstrated That Th Cells Of Acpamentioning
confidence: 99%
“…Indeed, citrullination critically regulates embryogenesis (21,22), epithelial-to-mesenchymal transformation (23), and pluripotency of embryonic stem cells (24). In addition, PAD4-mediated citrullination of histones is essential for the formation of neutrophil extracellular traps (NETs) (25)(26)(27), which can induce the expression of inflammatory cytokines, such as IL-6 and IL-18, as well as CCL20 and ICAM-1 from fibroblast-like synoviocytes (28).…”
Section: It Was Recently Demonstrated That Th Cells Of Acpamentioning
confidence: 99%
“…Besides, aberrant increase of PAD 4 has also been involved in multiple sclerosis, glaucoma and even cancers [10][11][12]. Therefore, with the deciphering the relation between PAD4 and different disease models [13,14], PAD4 has emerged as a potential therapeutic target for human diseases.…”
Section: Introductionmentioning
confidence: 99%
“…Other sites on GSK3β, such as Ser-48, -389, and -390, can also be phosphorylated, but their functions remain unknown (27). Besides phosphorylation, other modifications also regulate GSK3 activities, such as cleavage by calpain and by matrix metalloproteinase 2 leading to activated GSK3 fragments, mono-ADP ribosylation leading to GSK3 inhibition, and citrullination leading to nuclear localization of GSK3 (27,28). Recent work reported that mammalian GSK3β can be acetylated, and depletion of the deacetylase led to reduced phosphorylation and enhanced kinase activity of GSK3β (29).…”
mentioning
confidence: 99%